Requirements for renders on modern autoclaved aerated concrete. Issue 4 (1st September 2018) - Hartmann, Andrea; Loderer, Franz
Abstract: The development of modern autoclaved aerated concrete (AAC) leads to high thermal insulating masonry. Over the last years the reduction of the thermal conductivity of masonry units has been reached by reducing the bulk density and partly reducing the strength properties. AAC masonry is covered with an external rendering system to resist weathering and also to determine the appearance of the building. The structure of rendering systems is mainly influenced by the composition and characteristics of the substrate on which it shall be applied and to resist properly the impact of weathering. Looking to the future of the development of modern AAC with the aim to improve the material properties, for example, the thermal insulation, render systems for these modern AAC products have to be developed. "Modern renders" have to orient to the special properties and behavior of such wall materials not only because of lower densities and lower strength but also regarding deformation behavior.